2019
DOI: 10.18203/issn.2454-5929.ijohns20192706
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional temporalis fascia myringoplasty with fascia lata myringoplasty among patients with hearing loss

Abstract: <p class="abstract"><strong>Background:</strong> In selection of a graft tissue factors considered include its biological properties, probability of survival, its adequacy in size and ease of procurement<strong> </strong>The present study aims to preoperatively predict hearing improvement by paper patch test and compare with postoperative hearing improvement i.e. pre and post operatively hearing assessment.</p><p class="abstract"><strong>Methods:</strong> T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
2
5
1
Order By: Relevance
“…In each group there were 17 females (81%) and 4 males (19%). Our study had female predominance while studies done by Verma S et al 14 , Harkare VV et al 15 , showed male predominance. However gender distribution didn't have any effect on the study results.…”
Section: Sex Distributioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In each group there were 17 females (81%) and 4 males (19%). Our study had female predominance while studies done by Verma S et al 14 , Harkare VV et al 15 , showed male predominance. However gender distribution didn't have any effect on the study results.…”
Section: Sex Distributioncontrasting
confidence: 43%
“…In selection of a graft tissue, the factors considered include its biological properties, probability of survival, its adequacy in size and ease of procurement 13 . Temporalis fascia is the most widely used material for closure of tympanic membrane perforation 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Perforation size is an important determinant of the loss, larger perforations result in larger hearing losses. 3 80% of patients on our study was having moderate to large perforation which correspondence to degree of hearing loss.…”
Section: Resultsmentioning
confidence: 54%
“…The temporalis fascia had an overall graft uptake success rate of 90% which is lower than the study conducted by Verma et al (96%) and Indorewala et al (95%) [8,16]. But Dabholkar et al in underlay tympanoplasty achieved a graft success rate of 84% for temporalis fascia [17].…”
Section: Discussionmentioning
confidence: 68%
“…In the study conducted by Verma et al, audiological closure of the air-bone gap in the range of 0-30 dB was achieved in 88% cases of temporal fascia and 80% in fascia lata after surgery with no significant difference [16]. In 2014, Patil et al found that the mean gain in airbone gap postoperatively for temporalis fascia was 9.36 dB and for fascia lata was 12.1 dB which also was not significant [15].…”
Section: Discussionmentioning
confidence: 99%